Transforming Economic Education in Indonesia: Aligning Expectations and Realities - Kurniadi, Romi; Suratno, Suratno (Dinamika Pendidikan, 2023)
This study aims to investigate the extent of alignment between the expectations of the organization of economic education and the reality that exists, as a response to the shift in career choices of economic education alumni from the field of teaching and education. Through a qualitative research design using a document analysis approach, this study seeks to see trends in alumni employment profiles and graduate profiles based on economic education curriculum documents from 12 universities that organize economic education study programs. The results show that there is still a mismatch between the expectations of the graduate profile and the reality of the employment profile of economic education alumni. There needs to be an effort from higher education organizers to transform and readjust the competencies provided to the needs of alumni, society, and prospective users of graduates.